What is the pro-inflammatory dietary model associated with? - Grajek, Mateusz; Grot, Martina; Nigowski, Maciej; Kujawińska, Maria; Górski, Michał; Białek-Dratwa, Agnieszka; Krupa-Kotara, Karolina (Journal of Education, Health and Sport, 2022)
Introduction. Cellular potential disruption leads to several polyplatoligias due to increased systemic inflammation, as a consequence of the visualized multivariate appearance. Objective. To highlight the relevance of the pathomechanism of oxidative stress and oxidative potential about changes in metabolic mechanisms at the cellular level, predisposing to polypatoligia and the development of destructive transformations visualized in outward appearance targeted by a pro-inflammatory nutritional model. Material and methods. A sample of 226 subjects was selected by random selection of respondents. The author’s questionnaire concerned metric data, level of physical exercise, diagnosed disease entity, inflammatory changes within the body dermis, and level of frequency of consumption of selected food groups. The obtained results were verified by statistical analysis with a significance level of α <0.05. Results. The subject was characterized by a diagnosed multimorbidity at the level of (approximately 20%) about the individual clinical course of the respondent. The anthropometric parameter BMI without sex division (due to predominance of female subjects) among 55% of the whole group was within the normal range, constituting 24.4 kg/m2, showed a significant correlation directed at the pathomechanism of multimorbidity at the level of 78% in physical appearance. Conclusions. The pathomechanism of developing polyposis is significantly associated with the appearance of changes within the tissues translated into the shell system and anthropometric measurements related to the value of body mass index. Multivariable within the common coat is significantly dependent on the implemented phytotherapeutics - bioactive components derived from oregano, to obtain high antioxidant potential.